The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1021/la9815244
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Copper(II) Sulfate Pentahydrate Crystallization Using Ultrasound

Abstract: Ultrasound is beginning to be used to characterize many types of industrial two-phase dispersions, both suspensions and emulsions. It also has great potential as a process-monitoring tool alongside the well-established techniques of conductivity, pH, optical turbidity, tomography, and so forth. This paper describes a small volume test cell that has been developed to ultrasonically monitor the batch crystallization of a hydrated salt from saturated solution. The interaction of low-power, low-frequency (2− 7 MHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[9][10][11] More recent studies suggest the adoption of ultrasound attenuation, where rather spacious in-line probes have been developed, but a calibration is still required. [12][13][14] On the contrary, the focused beam reflectance measurement (FBRM) is carried out using a cylindrical probe that is easily applicable in crystallization vessels ranging from laboratory to production scale. [15][16][17][18] The FBRM provides on-line data of particle size and concentration in the form of a chord length distribution (CLD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] More recent studies suggest the adoption of ultrasound attenuation, where rather spacious in-line probes have been developed, but a calibration is still required. [12][13][14] On the contrary, the focused beam reflectance measurement (FBRM) is carried out using a cylindrical probe that is easily applicable in crystallization vessels ranging from laboratory to production scale. [15][16][17][18] The FBRM provides on-line data of particle size and concentration in the form of a chord length distribution (CLD).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the on-line monitoring of the solid phase in general and of the PSD in particular remains challenging. Laser diffraction has been used in most previous studies, but in this case sampling and dilution of the suspension are necessary. More recent studies suggest the adoption of ultrasound attenuation, where rather spacious in-line probes have been developed, but a calibration is still required. On the contrary, the focused beam reflectance measurement (FBRM) is carried out using a cylindrical probe that is easily applicable in crystallization vessels ranging from laboratory to production scale. The FBRM provides on-line data of particle size and concentration in the form of a chord length distribution (CLD). Although useful in general, CLD data cannot be converted directly into a PSD, i.e., they cannot be directly integrated into population balance modeling approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with SEM especially revealed that US spectroscopy reflects reality the best. The importance of the crystallization mechanism can be emphasized with regard to a study by Wilkinson et al 91 who investigated the crystallization of copper sulfate pentahydrate in a similar way as Tebbutt et al 92,93 Their results showed that the crystal size was strongly influenced by the cooling rate; however, at a size of roughly 300 μm the crystals break resulting in a similar PSD independent of the cooling rate. As mentioned before, Kippax et al emphasize the importance of accurate data for the physical properties of the particles and the liquid for the characterization of organic crystals by US attenuation spectroscopy as well.…”
Section: Ultrasonic Diagnosticsmentioning
confidence: 99%
“…There have been several attempts to use ultrasonic techniques to follow crystallization processes. For example, the change in crystal size distribution during crystallization of copper (II) sulfate pentahydrate from bulk (Tebbutt and others 1999) and seeded (Marshall and others 2002) solutions were calculated from ultrasonic spectra using scattering theories. However, the results showed some deviation from light scattering measurements.…”
Section: Introductionmentioning
confidence: 99%